1994
DOI: 10.1038/ki.1994.326
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of C-type natriuretic peptide receptors in human mesangial cells

Abstract: Our aim was to examine whether the human glomerulus was a target for C-type natriuretic peptide (CNP) and how A, B and C receptors of natriuretic peptides (ANPR-A, ANPR-B, ANPR-C) were distributed in glomerular mesangial and epithelial cells. CNP stimulated cyclic GMP production in cultured human mesangial and epithelial cells with similar threshold concentrations (1 nM) and maximum effects (basal value x 30 at 1 microM). In contrast, atrial natriuretic peptide (ANP) was only stimulatory in epithelial cells. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The existence of the NPR-A receptor was also suggested earlier by electrophysiological observations from these cells [34]. Using immunohistochemistry and PCR analysis it was suggested that the dominantly expressed natriuretic peptide receptor in human MCs is NPR-B [35,36]. These findings indicate marked species differences in the expression of receptors for natriuretic peptides.…”
Section: Discussionmentioning
confidence: 59%
“…The existence of the NPR-A receptor was also suggested earlier by electrophysiological observations from these cells [34]. Using immunohistochemistry and PCR analysis it was suggested that the dominantly expressed natriuretic peptide receptor in human MCs is NPR-B [35,36]. These findings indicate marked species differences in the expression of receptors for natriuretic peptides.…”
Section: Discussionmentioning
confidence: 59%
“…At the end of the incubation period, the supernatant was discarded. Intracellular cyclic AMP was extracted with an ethanol:formic acid mixture (95:5; v/v) and measured by radioimmunoassay as previously described [19]. …”
Section: Methodsmentioning
confidence: 99%
“…ANP-induced cGMP formation was regulated by protein kinase A (PKA), since H-89, a PKA inhibitor, decreased ANP-stimulated cGMP formation in podocytes (248). ANP, BNP, and CNP stimulated concentration-dependent cGMP formation, and in RT-PCR studies, mRNA for NPR-A, -B, and -C receptors was detected in human podocytes (514). The functional consequences of cGMP increase on podocytes are poorly understood.…”
Section: A Cgmp Signalingmentioning
confidence: 99%